2008
DOI: 10.1529/biophysj.108.136192
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Versions of the Myosin Relay Domain Differentially Respond to Load to Influence Drosophila Muscle Kinetics

Abstract: We measured the influence of alternative versions of the Drosophila melanogaster myosin heavy chain relay domain on muscle mechanical properties. We exchanged relay domain regions (encoded by alternative versions of exon 9) between an embryonic (EMB) isoform and the indirect flight muscle isoform (IFI) of myosin. Previously, we observed no effect of exchanging the EMB relay domain region into the flight muscle isoform (IFI-9b) on in vitro actin motility velocity or solution ATPase measurements compared to IFI.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 48 publications
0
38
0
Order By: Relevance
“…Interestingly, residue 509 varies among human muscle myosin isoforms as well, with the superfast extraocular myosin having a glutamic acid at this position compared with threonine in slower forms, suggesting a tighter linkage to the basic residue at position 759 in the faster myosin (44). We have shown that substitution of the entire relay domain of Drosophila IFI into an embryonic myosin isoform severely affects myosin function and myofibril stability (33), whereas the insertion of the embryonic relay into IFI impairs power generation in isolated fibers (45). It will be interesting to discern whether the two variable residues at the relay-converter interface play major roles in defining these functional properties.…”
Section: Discussionmentioning
confidence: 84%
“…Interestingly, residue 509 varies among human muscle myosin isoforms as well, with the superfast extraocular myosin having a glutamic acid at this position compared with threonine in slower forms, suggesting a tighter linkage to the basic residue at position 759 in the faster myosin (44). We have shown that substitution of the entire relay domain of Drosophila IFI into an embryonic myosin isoform severely affects myosin function and myofibril stability (33), whereas the insertion of the embryonic relay into IFI impairs power generation in isolated fibers (45). It will be interesting to discern whether the two variable residues at the relay-converter interface play major roles in defining these functional properties.…”
Section: Discussionmentioning
confidence: 84%
“…Lethocerus IFMs generates high forces at relatively low muscle speeds while Drosophila takes the high speed, low force approach. From mechanical measurements on isolated fibers, we know that Lethocerus IFMs generate about 40-fold higher isometric tension than Drosophila IFMs, ~120 and ~3 mN/ mm 2 , respectively (Agianian et al 2004; Yang et al 2008). The frequency at which Drosophila IFM maximum power is generated is ~150 Hz at 15 °C, compared to ~2–4 Hz for isolated Lethocerus fibers at 23 °C (Agianian et al 2004; Linari et al 2004; Ramanath et al 2011; Wang et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…A key aspect of the current study is that it allowed the analysis of naturally occurring isoforms that contain compatible alternative domains selected through evolution; this work complements and extends previous studies of the Drosophila relay and converter domains that relied on chimeric myosin molecules. 6,7,9,18,22,30,31 …”
Section: Discussionmentioning
confidence: 99%